LETRAMENTOS DIGITAIS: REFLEXÕES ACERCA DOS PROCESSOS DE ENSINO-APRENDIZAGEM - Fábio Narduchi de Paula; Alexandre de Jesus Pereira; Juliana Narduchi de Paula Mansur; Joaquim Oliveira (TRF2, 2018)
Faced with a new order of things, in which digital media and technologies increasingly occupy a special place in the ways of living and learning, it is urgent to reflect on the teaching and learning processes before so-called digital literatures. In the information network that surrounds us, several knowledge and very different forms of learning are mixed, while our educational system is still organized around the school and the book. In the midst of the new information society, two cultures converge: teachers ("digital aliens") and students ("digital natives"), who are confronted with diverse experiences in relation to digital technologies. The present bibliographic study aims to discuss the digital literacy for the teaching and learning processes, starting from the concept of literacy by Magda Soares and the desecration of Giorgio Agamben. We hope that, in this age of the internet, the teacher can make of his classroom a space of collective constructions, of shared learning, with Digital Information and Communication Technologies as the cornerstones of this process. Therefore, the desecration of the unfaithful is the political task of the coming generation.